Prediction of Salmon Inhibitor Peptides For DPP-IV Proteins Using Molecular Docking - Nahdiyah Vernanda Saputri; Yulanda Antonius (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Diabetes mellitus is the 3rd leading cause of death in Indonesia. Glucagon like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP) are incretin hormones that function in postpandrial insulin secretion. The purpose of this study was to determine potential peptides from salmon as DPP-IV inhibitors for antidiabetic drugs, using the molecular docking method. This study design refers to several in silico peptide design studies through a bioinformatics approach. The results showed that bioactive peptide molecules derived from salmon, as well as peptide 1 and peptide 2 were predicted as potential molecular peptides and had good interactions with DPP-IV proteins, and were proven to be able to inhibit the DPP-IV enzyme as a target for diabetes mellitus drugs through the identification and evaluation of molecular interactions that occurred using the in silico peptide protein-based molecular binding method. The conclusion is that bioactive peptide molecules derived from salmon, as well as peptide 1 and peptide 2 were predicted as potential molecular peptides and had good interactions with DPP-IV proteins and were proven to be able to inhibit the DPP-IV enzyme.